2006
DOI: 10.1136/bjo.2005.081422
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-106 plaque brachytherapy for symptomatic vasoproliferative tumours of the retina

Abstract: beta ray brachytherapy with (1106)Ru plaques was able to control the activity of VTR and retain vision. Cases with secondary glaucoma before treatment had a very poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 10 publications
1
55
0
10
Order By: Relevance
“…They are not considered to be hereditary, but one case report describes identical locations of bilateral VPRTs in two homozygotic twins (Wachtlin et al 2002). The majority of tumours (around 75%) are classified as idiopathic (Shields et al 1995;Damato 2006); secondary tumours are associated with multiple causes, such as uveitis (pars planitis), retinitis pigmentosa, toxoplasmosis, toxocara, retinopathy of prematurity (ROP), sickle cell retinopathy, Coats', ocular trauma, longstanding retinal detachment or retinal detachment surgery (Shields et al 1995;Lafaut et al 1999;Heimann et al 2000;Irvine et al 2000;Anastassiou et al 2006;Damato 2006;Tranos et al 2006). A solitary tumour is the most common finding, but multiple and diffuse tumour types also occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are not considered to be hereditary, but one case report describes identical locations of bilateral VPRTs in two homozygotic twins (Wachtlin et al 2002). The majority of tumours (around 75%) are classified as idiopathic (Shields et al 1995;Damato 2006); secondary tumours are associated with multiple causes, such as uveitis (pars planitis), retinitis pigmentosa, toxoplasmosis, toxocara, retinopathy of prematurity (ROP), sickle cell retinopathy, Coats', ocular trauma, longstanding retinal detachment or retinal detachment surgery (Shields et al 1995;Lafaut et al 1999;Heimann et al 2000;Irvine et al 2000;Anastassiou et al 2006;Damato 2006;Tranos et al 2006). A solitary tumour is the most common finding, but multiple and diffuse tumour types also occur.…”
Section: Introductionmentioning
confidence: 99%
“…vessels, with hyalinized vessel walls, exudates and haemorrhages (Irvine et al 2000). Macroscopically the tumours are heterogenous in appearance, probably because of a varying amount of glia and blood vessels (Anastassiou et al 2006). The tumours are characterized by having yellowish or pinkish colour, pathological blood vessels and exudations.…”
Section: Introductionmentioning
confidence: 99%
“…Primary tumors correspond from 53 to 80% of the cases in the major reported series (7,9,13) . RVPT affects patients of both genders and all ages, but there is a predominance of women after the 5 th decade (7,8,13) . Most patients seek medical attention complaining of decrease in visual acuity, although some cases are discovered on routine evaluation (713) .…”
Section: Clinical Picture and Differential Diagnosismentioning
confidence: 98%
“…RVPT can be primary (idiopathic) or secondary (associated) to other ocular diseases like retinitis pigmentosa, sickle cell retinopathy, Coat's disease, retinopathy of prematurity, toxoplasmosis, toxocariasis, tu berculosis, other uveitis, ocular trauma, retinalchoroidal coloboma and retinal detachment (13,713) . Primary tumors correspond from 53 to 80% of the cases in the major reported series (7,9,13) .…”
Section: Clinical Picture and Differential Diagnosismentioning
confidence: 99%
“…Many lesions can be effectively managed using triple freeze thaw transconjunctival cryotherapy. 8 Recent studies have also demonstrated that larger lesions can be treated with either ruthenium 106 26 or iodine 27 -plaque brachytherapy. A number of case reports have also appeared in the literature advocating the use of a photodynamic therapy to treat both primary 28,29 and secondary 10 vasoproliferative tumours.…”
Section: Treatmentmentioning
confidence: 99%